2011
DOI: 10.1021/je101262w
|View full text |Cite
|
Sign up to set email alerts
|

Fourier Transform Infrared Spectroscopic Analysis of Fruit Peels before and after the Adsorption of Heavy Metal Ions from Aqueous Solution

Abstract: For orange peel (OP), lemon peel (LP), and banana peel (BP) as adsorbents for removal of heavy metal ions such as Cu2+, Ni2+, Cd2+, Pb2+, and Zn2+ from aqueous solution, a simple FT-IR technique was used and discussed to study the variation in functional groups upon modification. Metal−carbon bond formation was witnessed by FT-IR during metal ion adsorption. All of these adsorbents were characterized by FT-IR, BET, and SEM. The presence of carboxylic and hydroxyl groups was confirmed by FT-IR. The FT-IR spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(62 citation statements)
references
References 23 publications
6
50
0
6
Order By: Relevance
“…1 Zeta potential of the EFBB and RHB measured at different pHs groups because its outer orbital electrons are completely filled-hence the decreased adsorption of Zn by the biochars. Pb has the fewest electrons in its outermost valence shell among the heavy metals studied; thus, it can bind with functional groups with donor sites better than Cu and Zn (Thirumavalavan et al 2011). The result of this study is in agreement with the result of Zhua et al (2012) who reported that metals adsorption onto xanthate-modified magnetic chitosan followed the order of Pb(II) [ Cu(II) [ Zn(II).…”
Section: Batch Equilibrium Adsorptionsupporting
confidence: 90%
See 3 more Smart Citations
“…1 Zeta potential of the EFBB and RHB measured at different pHs groups because its outer orbital electrons are completely filled-hence the decreased adsorption of Zn by the biochars. Pb has the fewest electrons in its outermost valence shell among the heavy metals studied; thus, it can bind with functional groups with donor sites better than Cu and Zn (Thirumavalavan et al 2011). The result of this study is in agreement with the result of Zhua et al (2012) who reported that metals adsorption onto xanthate-modified magnetic chitosan followed the order of Pb(II) [ Cu(II) [ Zn(II).…”
Section: Batch Equilibrium Adsorptionsupporting
confidence: 90%
“…The absorption of Pb was highest for both biochars, followed by Cu and Zn. This can be explained by the fact that both Pb and Cu can easily react with functional groups containing unshared pairs of electrons such as those in O, N, P, and S. Additionally, Pb and Cu have a greater affinity for carboxyl groups than does Zn (Thirumavalavan et al 2011). Hence, Pb and Cu can easily coordinate with both the carboxyl and hydroxyl groups of the biochars, as the functional groups have valence shell electrons in the outer orbital.…”
Section: Batch Equilibrium Adsorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The maximum absorption ability according to the Langmuirmodel was 3.18 mmol/g (658 mg/g), which was reported very high for other biosorbents and similar to some ion interchange resins. Besides these, several other researchers also examined citrus husks or lemon husks as adsorbents for varied aquatic Contaminants elimination [60].…”
Section: Bio-waste Materials As Adsorbent Of Contaminate From Waste Wmentioning
confidence: 99%